The register as a tool for researching trends in phlebological care for the population of a large industrial center of Russia - E. P. Burleva; A. V. Peshkov; S. A. Tyurin; S. M. Belentsov; O. A. Vinogradov; A. Yu. Leshchinskaya; O. A. Lobut; A. A. Zasorin (Амбулаторная хирургия)
Introduction. The Russian Phlebological Register began work in 2016 under the patronage of the Association of Phlebologists of Russia. The creation of a phlebological register in a separate municipal center of the country complements and enriches national plans. Aim. Тo investigate the trends in the organization of medical care to the population with chronic venous diseases (CVD) of a large industrial center using the phlebological register over the past 20 years. Materials and methods. The data of municipal and private medical institutions of Ekaterinburg from 2003 to 2022 are analyzed. Data on municipal hospitals (MHs) are provided by the TFOMS of the Sverdlovsk region. Data on private medical centers (PMCs) are obtained by exporting them from the electronic databases of each center. The statistics of phlebectomies (PhE), outpatient minimally invasive interventions and procedures are summarized. Results. Over the entire period of time, the number of classical phlebectomies in MHs decreased by 4 times – from 2300 (2003) to 587 (2022). At the same time, the development of minimally invasive procedures on the main veins in the PMCs increased from 313 (2003) to 4364 (2022). This made it possible to double the coverage of patients suffering from CVD with specialized medical care. In the structure of patients operated in MHs, the proportion of persons with severe chronic venous insufficiency (CVD C4–6) significantly decreased. The number of patients with superficial thrombophlebitis had a steady downward trend: the first 5 years (2003–2007) – about 200 PhE/year, then 5 years (2008–2012) – about 120 PhE/year, and from 2013 to 2022 < 100 PhE/year. Discussion. Private medical centers have consistently introduced the latest technologies, but endovasal laser coagulation remains the leader. Conclusion. The analysis of the register revealed a number of systemic changes in the organization of phlebological care.